Prelude to lithuanian mathematical studies: Higher courses in Kaunas - Banionis, Juozas (Lietuvos matematikos rinkinys, 2021)
As soon as the young Lithuanian state was formed, the international situation was unfavorable (the war of independence took place) and as a result its internal life was burdened by difficulties. Therefore, the Lithuanian intelligentsia (one of their leading mathematicians Z. Žemaitis) took the initiative to organize Higher Courses (AK) in the temporary capital Kaunas. These universal courses, equivalent to the type of higher education institution (university), existed in 1920– 1922. According to the adopted statute, there were six chapters covering the basic sciences - humanities, social sciences and natural or real sciences. The existence of the latter sciences was evidenced by the Department of Mathematics and Physics, where there was an opportunity to study mathematics in Lithuanian. This article shows the circumstances of the establishment of AK, the conditions of their activity, introduces the lecturers of mathematics and shows the composition of the listeners, as well as reveals the content of mathematics studies and names the literature used for studies. During the two years of AK’s existence, a solid foundation was laid for the future Lithuanian University (since 1930 – Vytautas Magnus). The staff formed consisted mainly of 1922. the core of the developing university, and the first scientific aids, books and premises were acquired - the base of the higher school. For the first time in its history, AK turned Kaunas into a university city, and the departments operating in them laid the foundations for the establishment of the university, as well as the Faculty of Mathematics.